Answer:
The proof makes use of congruences as follows:
Explanation:
We can prove this result using congruences module 3. First of all we shall show that
for all
. By induction we have
. For
we have
![2^(4-1)=8\equiv 2 \pmod{3}](https://img.qammunity.org/2020/formulas/mathematics/college/tvsl6zpn4lu5n9ru7w8mtgntz21qoyyrgx.png)
- Suppose that the statement is true for
and let's prove that it is also true for
. In fact,
![2^(2(k+1)-1)=2^(2k-1+2)=2^(2k-1)2^(2)\equiv 2\cdot 2^(2)\equiv 8 \equiv 2 \pmod{3}](https://img.qammunity.org/2020/formulas/mathematics/college/pyjril94lammz6268s0e6alsybbfr6s84j.png)
Then induction we proved that
for all
. Then
![2^(2n-1)+1\equiv 2+1\equiv 3\equiv 0 \pmod{3}](https://img.qammunity.org/2020/formulas/mathematics/college/puxdhyd11j2txz1qhpwzvk6v3fyyq001zj.png)
From here we conclude that the expression
is divisible by 3.